Changes in community pharmacists' knowledge, attitudes, and practice regarding the management of hypertension before and after educational interventions. (18th May 2020) - Noda, Aoi; Obara, Taku; Takada, Kazuki; Kishikawa, Yukinaga; Abe, Shinya; Yoshimachi, Shoko; Mano, Nariyasu; Imai, Yutaka; Goto, Teruaki
ABSTRACT: Objective: To clarify changes in community pharmacists' knowledge, attitudes, and practice regarding the management of hypertension before and after attending educational interventions based on their self-report on a questionnaire survey. Method: We conducted questionnaire surveys regarding the management of hypertension with a sample of community pharmacists before and after educational interventions. Results: The proportions of pharmacists who knew the 2014 Japanese Society of Hypertension Guidelines, guidelines for home blood pressure measurement, reference values for hypertension based on clinic-measured blood pressure, and reference values for hypertension based on home-measured blood pressure after the educational interventions (59.3%, 41.4%, 75.1%, and 70.8% respectively) were significantly higher relative to those recorded before interventions (31.6%, 13.7%, 47.7%, and 25.4% respectively). Conclusions: These findings suggest that in-house training might increase the knowledge of community pharmacists regarding hypertension management.